The linguistic analysis of the memoir (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The linguistic analysis of the memoir is carried out in the article, the presence of genre and style features of memoir literature is proved, text structure and verbal representation forms of the contents are defined, the specificity of memoir speech organization is clarified, and the worldview and artistic attitude of the memoirist is grounded.
Keywords: linguistic analysis of the text; memoir literature; speech genres; genre and style features; types of speech communication